Gene-Based Therapies for Leber Hereditary Optic Neuropathy. Hype or Hope?. Issue 4 (July 2016) - Mackey, David A.; Kearns, Lisa S.; Hewitt, Alex W.
Abstract : Abstract: Leber hereditary optic neuropathy has now joined Leber congenital amaurosis in the list of genetic eye diseases undergoing gene therapy clinical trials. Although a dramatic response to treatment would be welcome, a minor improvement in vision is a major challenge in efficacy assessment, given this may occur spontaneously as part of the natural history of minor recovery in some patients. Thus, we must await the outcome of adequately powered clinical trials to know if the treatment is effective, particularly given the likely high cost of such therapeutic interventions in the future. We need global cooperation to ensure that the most suitable patients are enrolled in these trials and that support is provided for participants who need to travel from the Asia-Pacific region to Europe or North America if there are no local arms of these trials.